GROWING SOCIAL ENTREPRENEURSHIP OF SILIWANGI UNIVERSITY STUDENTS THROUGH THE SILIWANGI SOCIAL BUSINESS LEAGUE (LIBSOS) PROGRAM IN SELAMANIK VILLAGE, CIAMIS - Azhari, Septian Cahya; Sudrajat, Zulfi Gumilang; Fauzi, Rizki Syamsul; Rosidah, Euis (LPPM Univ. Ibn Khaldun Bogor, 2023)
The entrepreneurial system of capitalism that is now widely applied in various corporate sectors is not a little bit only profitable in terms of monetary parts of some companies or individuals. In competing with the economic system of capitalism that causes social inequality, the concept of social entrepreneurship is a solution to build healthier companies. This article presents the participation of the government and universities in building social entrepreneurship through social entrepreneurial innovations carried out by Siliwangi University students. A descriptive qualitative approach is used to explain social entrepreneurship training activities (LIBSOS). Through the establishment of social entrepreneurship pioneered by universities, innovative social entrepreneurship will grow and develop as a way to overcome socio-economic inequality in society.